Longitudinal Cohort Study of Interpersonal Violence Among College-Aged Men and Women, United States, 2019-2020 - Cantor, David ([Verlag nicht ermittelbar], 2021)
The extent and consequences of various forms of interpersonal violence (IV) among college-aged persons has been well-documented. This study sought to examine how IV might differ between young adults who go to college compared to those that do not go to college. To better understand the risks for, experiences with, and consequences of IV among young adults, in fiscal year 2016, the National Institute for Justice (NIJ) made an award to Westat to fund the planning phase of a longitudinal study to research the victimization and violence experienced by college-aged individuals. The planning phase was designed to produce a comprehensive plan to conduct a generalizable, longitudinal study examining long-term trajectories of risk for, experiences with, and recovery after experiencing violence and victimization among college-aged individuals. This pilot study was the result of this planning phase. The major variables in this study contained information regarding sexual assault and rape, dating violence, stalking, violence committed by peers, and violence committed by strangers, as well as demographic variables such as participant age, gender, and race.